Effects of cutting traits and competition on performance and size hierarchy development over two cutting cycles in willow. (January 2018) - Edelfeldt, Stina; Lundkvist, Anneli; Forkman, Johannes; Verwijst, Theo
Abstract: To assess if cutting traits (clone, fresh weight) in combination with strong competition from adjacent willows (planted in monoclonal stands and clonal mixtures) affected performance and size hierarchy development in willow during consecutive harvests, a field experiment was performed in central Sweden during 2008–2015. Cuttings from five Salix clones were planted in 1.8 m × 1.8 m plots, at a density of 197 500 cuttings ha −1 in monoculture and in ten mixtures using two clones (i.e. 15 combinations). Maximum height was measured each year and the experiment was harvested after the growing seasons 2012 and 2014. Larger cuttings produced stools with lower death rate, higher maximum height and larger biomass production compared to smaller cuttings. The high competition pressure resulted in 9.2% stool death at harvest 2012 and 39% stool death at harvest 2014. Tora ( Salix schwerinii x Salix viminalis ) showed the highest performance and Jorr ( Salix viminalis ) and Gudrun ( Salix dasyclados ) the lowest. Planting system had less effect on stool death, height development and biomass production. Tora was the only clone producing more biomass when grown in mixtures compared to monoculture. The size hierarchy between individual stools was generally kept during the experimental period in both monocultures and mixtures, even if the height correlations decreased with year. To obtain a more even establishment of willow stands and lower the risk of a size hierarchy developing leading to large stool mortality and gaps in the stand, we recommend the use of larger and more even-sized cuttings. Highlights: The size hierarchy was generally kept during the experimental period. The competitive pressure was high, stool death being 9.2% in 2012 39% in 2014. Willow cutting size strongly influenced performance and size hierarchy development. Clone mixture was of less importance to performance and hierarchy development. Tora showed the highest performance and Jorr and Gudrun the lowest.